MODEL TRANSFORMASI SAMPAH CANGKANG KERANG DI PERMUKIMAN KAWASAN PESISIR WATUKARUNG, PACITAN: STUDI ETNOARKEOLOGI - Martias, Irsyad (Berkala Arkeologi, 2012)
Ecofact is a key for investigating mode of adaptation. Ecofact that commonly found on archaeological sites especially on inhabited caves were shell deposits. Fundamentally, the formation of archaeological record was resulted from behavioral processes and transformational processes. However, the problem is that we can’t observe them, because those aspects had occurred in past time. Etnoarchaeological study can be used to solve those problems. Ethnoarchaeology studies have given contribution to interpret various aspects of human life of the past, starting from issues related to the technological and tools systems, subsistence, social systems, and processes of transformation. Therefore, this ethnoarchaeological research investigates behavioral system of coastal community who has collected, consumed, and discarded sea shells. The result of this research can be used as a model from formation processes of sea shell ecofact.